Adsorpsi Isothermal Hidrogen Pada Karbon Aktif Berbahan Dasar Cangkang Sawit Pada Temperatur 45 oC - Fakhru Rozi Z; Awaludin Martin; Nasruddin Nasruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Hydrogen is one of the promising renewable energy and potential subtitute for fossil fuels in the future. Hydrogen has short comings in its application as fuel is in storage. The study resulted in the capacity of hydrogen adsorption on activated carbon made from palm shells. Data were collected by volumetric method in the isothermal adsorption process. Adsorption isotherm temperature is performed at 45oC at pressures up to 30 bar. The maximum adsorption capacity at isotherm temperatures 45oC is 2.03x10-3 kg/kg mass of adsorbent at a pressure of 30.13 bar. Subsequently correlated the data obtained using the Langmuir model equation, Toth and Langmuir-Freundlich. Deviation from the Langmuir equation, Toth and Langmuir-Freundlich obtained was 16.72.77%, 15.97% and 9.79%.Keywords: Hydrogen Adsorption, Volumetric Method, Isotherm Adsorption